Antimony molybdate nanosheet and preparation method thereof, modified ABS (Acrylonitrile Butadiene Styrene) resin as well as preparation method and application thereof
Through the hydrothermal preparation and melt blending technology of antimony molybdate nanosheets, the problem of the poor flame retardant and smoke suppression effect of existing nanofire retardant materials on ABS resin is solved, and the efficient flame retardant and mechanical performance improvement of ABS resin is achieved .
Patent Information
- Application Number
- CN202411555528.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-01-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing nanofire retardant materials have poor flame retardant and smoke inhibiting effects on acrylonitrile-butadiene-styrene (ABS) resins, and it is difficult to effectively inhibit heat and smoke release.
Antimony molybdate nanosheets are prepared by hydrothermal reaction, combined with cationic surfactant to adjust the nanosheet layer structure to form a stacked structure to block heat transfer and decomposition products during combustion, and then melt blended with ABS resin to improve flame retardant performance.
It significantly reduces the heat release rate and smoke release rate of ABS resin, improves the flame retardant performance, effectively suppresses the rapid combustion of the ABS matrix, and enhances the tensile strength and carbonization performance of ABS resin.
Smart Images

Figure CN119284956A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of flame retardant materials, and specifically relates to an antimony molybdate nanosheet and a preparation method thereof, a modified ABS resin and a preparation method and application thereof. Background Art
[0002] In recent years, nano flame retardant technology has become an important research hotspot in the field of flame retardancy. Since nanocomposites can not only improve flame retardancy but also other properties (such as mechanical properties) compared with traditional flame retardant materials, the application prospects of nanomaterials in flame retardancy are very attractive. Nanoparticles such as nanoclay, carbon nanotubes (CNTs), layered double hydroxides, and graphene have attracted widespread attention due to their flame retardant and smoke suppression effects on acrylonitrile-butadiene-styrene (ABS).
[0003] In addition, as a nanoparticle synergistic flame retardant, antimony oxide (Sb2O3) can significantly improve the flame retardant properties of composite materials. For example, Sb2O3 flame retardant synergistic with brominated epoxy resin (BEO), zinc hydroxystannate (ZHS) and MMT (montmorillonite) flame retardant composite materials produce catalytic crosslinking in the condensed phase, thereby improving thermal stability and residual carbon content. At the same time, the combustible volatile products are diluted, the free radicals in the gas phase are captured, and the gas phase and the condensed phase work together to produce a flame retardant effect.
[0004] However, the flame retardant and smoke suppression effects of the above materials on ABS are relatively poor, such as the release of heat and smoke. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide an antimony molybdate nanosheet and a preparation method thereof, a modified ABS resin and a preparation method and application thereof. The antimony molybdate nanosheet provided by the present invention has good flame retardant properties and can effectively inhibit the rapid combustion of the ABS resin matrix.
[0006] In order to achieve the above object, the present invention provides the following scheme:
[0007] The present invention provides a method for preparing antimony molybdate nanosheets, comprising the following steps:
[0008] The cationic surfactant, antimony salt, molybdate and water are mixed and subjected to a hydrothermal reaction to obtain the antimony molybdate nanosheets; the temperature of the hydrothermal reaction is 160-210°C.
[0009] Preferably, the cationic surfactant includes one or more of cetyltrimethylammonium bromide, dodecyltrimethylammonium chloride and cetylpyridinium chloride; the molar ratio of the cationic surfactant to the molybdenum in molybdate is (0.5-0.7):1.
[0010] Preferably, the antimony salt includes antimony trichloride and / or antimony nitrate; the molybdate includes one or more of sodium molybdate, ammonium molybdate and potassium molybdate; and the molar ratio of antimony in the antimony salt to molybdenum in the molybdate is 2:(1-1.2).
[0011] Preferably, the hydrothermal reaction time is 6 to 18 hours.
[0012] The present invention provides antimony molybdate nanosheets prepared by the preparation method described in the above scheme, wherein the sheet diameter of the antimony molybdate nanosheets is ≤500nm.
[0013] The present invention provides a modified ABS resin, comprising an ABS resin matrix and antimony molybdate nanosheets dispersed in the ABS resin matrix; the antimony molybdate nanosheets are the antimony molybdate nanosheets described in the above scheme.
[0014] Preferably, the mass of the antimony molybdate nanosheets is 1-10% of the mass of the modified ABS resin.
[0015] The present invention provides a method for preparing the modified ABS resin described in the above scheme, comprising the following steps:
[0016] The antimony molybdate nanosheets and the ABS resin matrix are melt-blended to obtain the modified ABS resin.
[0017] Preferably, the melt blending temperature is 180-210° C. and the time is 10-18 min.
[0018] The invention provides the use of the modified ABS resin described in the above scheme or the modified ABS resin prepared by the preparation method described in the above scheme in flame retardancy and smoke suppression.
[0019] The present invention provides a method for preparing antimony molybdate (Sb2MoO6) nanosheets, comprising the following steps: mixing a cationic surfactant, an antimony salt, a molybdate salt and water, and performing a hydrothermal reaction to obtain the antimony molybdate nanosheets. The cationic surfactant of the present invention is used as a structural regulator of nanoparticles, so that antimony molybdate forms a unique nanosheet layer structure (mainly because the cationic part of the cationic surfactant regulates the dispersibility of the nanosheets, so that the antimony molybdate nanosheets form a stacking structure), blocks heat transfer during the combustion process when flame retardant, delays the decomposition of the composite material, and blocks the diffusion of decomposition products into the gas phase.
[0020] The present invention provides a modified ABS resin, comprising an ABS resin matrix and antimony molybdate nanosheets dispersed in the ABS resin matrix. The present invention improves the tensile strength of the ABS resin matrix because the Sb2MoO6 nanosheets have good dispersibility and interface interaction in the ABS resin matrix. The results of the embodiment show that the peak heat release rate (PHRR) of ABS / AM5 (representing that the mass of Sb2MoO6 accounts for 5% of the total mass of Sb2MoO6 and the ABS resin matrix) and ABS / AM10 (representing that the mass of Sb2MoO6 accounts for 10% of the total mass of Sb2MoO6 and the ABS resin matrix) are 19.7% and 32.9% lower than that of ABS, respectively. The inhibition rates of ABS / AM5 and ABS / AM10 on the peak smoke release rate (PSPR) are 19.7% and 32.4%, respectively, indicating that the Sb2MoO6 nanosheets have an inhibitory effect on heat release and smoke release.
[0021] The Sb2MoO6 nanosheets provided by the present invention have good physical barrier effect in the condensed phase, and can protect the inner layer of the ABS resin from further pyrolysis and combustion. The results of the embodiment show that the Sb2MoO6 nanosheets have good flame retardant properties and can effectively inhibit the rapid combustion of the ABS matrix. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0023] Figure 1 XRD pattern (a) and SEM image (b) of the Sb2MoO6 sample of Comparative Example 1;
[0024] Figure 2 SEM images of the Sb2MoO6 sample AM-6h (a) of Example 2, the Sb2MoO6 sample AM-9h (b) of Example 3, the Sb2MoO6 sample AM-12h (c) of Example 1, the Sb2MoO6 sample AM-15h (d) of Example 4, and the Sb2MoO6 sample AM-18h (e) of Example 5;
[0025] Figure 3The XRD spectra of the Sb2MoO6 samples synthesized at different reaction times in Examples 1 to 5 (a) are compared with the JCPDS database of Sb2MoO6, the full XPS spectrum of the Sb2MoO6 sample in Example 1 (b), the Sb3d spectrum of the Sb2MoO6 sample in Example 1 (c), the O1s spectrum of the Sb2MoO6 sample in Example 1 (d), and the Mo3d spectrum of the Sb2MoO6 sample in Example 1 (e);
[0026] Figure 4 TEM images (ac, h) of Sb2MoO6 of Example 1, STEM-HAADF image (d) of Sb2MoO6 of Example 1, and elemental images of Mo, Sb, and O in the corresponding regions (e-g);
[0027] Figure 5 TEM images of ABS / AM1 (a) of Application Example 1, ABS / AM5 (b) of Application Example 3, and ABS / AM10 (c) of Application Example 4; XRD patterns of pure ABS and ABS composites (d); stress-strain curves (e) and mechanical property parameter comparison diagrams of ABS / AM composites (f);
[0028] Figure 6 The ABS / AM composite materials of Application Examples 1 to 4, pure ABS and the Sb2MoO6 sample of Example 1 (i.e. Figure 6 TG (a) and DTG (b) curves of AM in air atmosphere;
[0029] Figure 7 (a) heat release rate curves of ABS and ABS / AM samples of Application Examples 1 to 4, and (b) smoke generation rate curves;
[0030] Figure 8 The SEM images of carbon residues of ABS / AM composite materials: the upper and lower rows are ABS / AM1, ABS / AM5, and ABS / AM10 respectively;
[0031] Fig. 9 The XPS full spectrum (b) and Sb3d (c), O1s (d) and Mo3d (e) spectra of the ABS / AM10 carbon residue of Application Example 4;
[0032] Fig.10 FTIR spectra of carbon residues of ABS and ABS composite materials. DETAILED DESCRIPTION
[0033] The present invention provides a method for preparing antimony molybdate nanosheets, comprising the following steps:
[0034] The cationic surfactant, antimony salt, molybdate and water are mixed and subjected to a hydrothermal reaction to obtain the antimony molybdate nanosheets.
[0035] Unless otherwise specified, the materials and equipment used in the present invention are commercially available products.
[0036] In the present invention, the cationic surfactant preferably includes one or more of cetyl trimethyl ammonium bromide, dodecyl trimethyl ammonium chloride and cetyl pyridinium chloride; the molar ratio of the cationic surfactant to the molybdenum in the molybdate is preferably (0.5-0.7):1, and in the embodiments of the present invention, it can be specifically 0.5:1, 0.55:1, 0.6:1 or 0.7:1. The cationic surfactant of the present invention acts as a structural regulator of nanoparticles, so that antimony molybdate forms a unique nanosheet structure (mainly because the cationic part of the cationic surfactant regulates the dispersibility of the nanosheets, so that the antimony molybdate nanosheets form a stacking structure), blocks the heat transfer during the combustion process when flame retardant, delays the decomposition of the composite material, and blocks the diffusion of decomposition products into the gas phase.
[0037] In the present invention, the antimony salt preferably includes antimony trichloride and / or antimony nitrate; the molybdate preferably includes one or more of sodium molybdate, ammonium molybdate and potassium molybdate; the molar ratio of antimony in the antimony salt to molybdenum in the molybdate is preferably 2:(1-1.2), and in the embodiments of the present invention, it can specifically be 2:1 or 2:1.2.
[0038] In the present invention, the temperature of the hydrothermal reaction is 160-210°C. In an embodiment of the present invention, it can be 160°C, 170°C, 180°C, 190°C, 200°C or 210°C. The time of the hydrothermal reaction is preferably 6-18h. In an embodiment of the present invention, it can be 6h, 8h, 9h, 10h, 12h, 15h or 18h.
[0039] In the present invention, the mixing of the cationic surfactant, antimony salt, molybdate and water preferably comprises: subjecting the cationic surfactant and water to a first mixing ultrasound, then adding the antimony salt and molybdate, and subjecting the second mixing ultrasound.
[0040] In the present invention, the mass ratio of the cationic surfactant to the volume of water is preferably 2.5 mg: 1 mL. In the present invention, the time of the second mixed ultrasound is preferably 10 min. The present invention can dissolve the cationic surfactant in water through the first mixed ultrasound; the present invention can evenly disperse the antimony salt and molybdate in water through the second mixed ultrasound.
[0041] After the hydrothermal reaction is completed, the present invention preferably washes the obtained reaction solution with water and ethanol, then collects the precipitate by centrifugation, and obtains the antimony molybdate nanosheets through drying and grinding.
[0042] In the present invention, the drying temperature is preferably 60° C. and the drying time is preferably 12 hours.
[0043] The present invention provides antimony molybdate nanosheets prepared by the preparation method described in the above scheme, wherein the sheet diameter of the antimony molybdate nanosheets is ≤500nm.
[0044] The present invention provides a modified ABS resin, comprising an ABS resin matrix and antimony molybdate nanosheets dispersed in the ABS resin matrix; the antimony molybdate nanosheets are the antimony molybdate nanosheets described in the above scheme. The present invention has no special requirements for the ABS resin matrix, and any material known in the art can be used.
[0045] In the present invention, the mass of the antimony molybdate nanosheets is preferably 1-10% of the mass of the modified ABS resin. In an embodiment of the present invention, it can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%.
[0046] In the present invention, the addition of Sb2MoO6 nanosheets promotes the carbonization of the modified ABS resin, thereby increasing the fireproof performance of the ABS resin matrix. At the same time, with the addition of Sb2MoO6, the carbon structure becomes dense and continuous, and the formation of this dense carbon helps to suppress the heat release and smoke generation during the combustion process; the Sb2MoO6 nanosheets act in the condensed phase during the combustion process, thereby improving the fire safety of the modified ABS resin.
[0047] The present invention provides a method for preparing a modified ABS resin, comprising the following steps:
[0048] The antimony molybdate nanosheets and the ABS resin matrix are melt-blended to obtain the modified ABS resin.
[0049] In the present invention, the temperature of the melt blending is preferably 180-210°C, and in the embodiments of the present invention, it can be 180°C, 190°C, 200°C or 210°C; the time of the melt blending is preferably 10-18 minutes, and in the embodiments of the present invention, it can be 10 minutes, 12 minutes, 14 minutes, 15 minutes or 18 minutes. In the present invention, the melt blending is preferably carried out under stirring, and the stirring speed is preferably 60 rpm.
[0050] The present invention can make the antimony molybdate nanosheets evenly distributed in the ABS resin matrix through melt blending.
[0051] The present invention provides the use of the modified ABS resin described in the above scheme or the modified ABS resin prepared by the preparation method described in the above scheme in flame retardancy and smoke suppression. In the present invention, the modified ABS resin can be specifically applied to electrical appliances, such as a TV housing or a switch housing.
[0052] The present invention improves the tensile strength of the ABS resin matrix because the Sb2MoO6 nanosheets have good dispersibility and interface interaction in the ABS resin matrix. The results of the embodiment show that the peak heat release rate (PHRR) of ABS / AM5 (representing that the mass of Sb2MoO6 accounts for 5% of the total mass of Sb2MoO6 and the ABS resin matrix) and ABS / AM10 (representing that the mass of Sb2MoO6 accounts for 10% of the total mass of Sb2MoO6 and the ABS resin matrix) are 19.7% and 32.9% lower than that of ABS. The inhibition rates of ABS / AM5 and ABS / AM10 on the peak smoke release rate (PSPR) are 19.7% and 32.4% respectively, indicating that the Sb2MoO6 nanosheets have an inhibitory effect on heat release and smoke release.
[0053] The Sb2MoO6 nanosheets provided by the present invention have good physical barrier effect in the condensed phase, and can protect the inner layer of the ABS resin from further pyrolysis and combustion. The results of the embodiment show that the Sb2MoO6 nanosheets have good flame retardant properties and can effectively inhibit the rapid combustion of the ABS matrix.
[0054] In order to further illustrate the present invention, an antimony molybdate nanosheet and a preparation method thereof, a modified ABS resin and a preparation method and application thereof provided by the present invention are described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0055] The ABS resin used in the examples was purchased from Tianjin Dagu Chemical Co., Ltd.; hexadecyltrimethylammonium bromide (CTAB), antimony trichloride (SbCl3), sodium molybdate, and dihydrate (Na2MoO4·2H2O) were all purchased from Sinopharm Chemical Reagent Co., Ltd.; and anhydrous ethanol (C2H5OH) was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0056] Example 1
[0057] Sb2MoO6 nanostructures were synthesized by hydrothermal method using CTAB as cationic surfactant, SbCl3 as Sb source, and Na2MoO4·2H2O as Mo source. CTAB (200 mg) was dissolved in 80 mL deionized water solution by ultrasound, and then SbCl3 (2 mmol) and Na2MoO4·2H2O (1 mmol) were added to the above solution and ultrasound was applied for 10 min to ensure that all reagents were evenly dispersed. The precursor solution with cyan was then transferred to a 100 mL autoclave and placed in a 180 ° C drying oven for 12 h. After the reactor cooled to room temperature, it was thoroughly washed with water and ethanol, and the green precipitate was collected by centrifugation. Finally, it was dried in a 60 ° C drying oven for 12 h and ground to obtain a green powder product Sb2MoO6 nanosheet, which was recorded as AM-12.
[0058] Embodiments 2 to 5
[0059] The preparation steps are the same as those in Example 1, except that the reaction times are 6 h, 9 h, 15 h and 18 h, respectively, to obtain Sb2MoO6 nanosheets, which are denoted as AM-6, AM-9, AM-15 and AM-18, respectively.
[0060] Comparative Example 1
[0061] The preparation steps are the same as those in Example 1, except that CTAB is not added, and a green powder product Sb2MoO6 is obtained.
[0062] Application Example 1
[0063] The composites were pre-dispersed by melt blending using a Thermo Hakker rheometer (temperature: 200°C, time: 15 min, rotor speed: 60 rpm).
[0064] Specifically, the Sb2MoO6 nanosheets prepared in Example 1 and the ABS resin matrix are mixed and melt blended using a ThermoHakker rheometer. The melt blending temperature is 200°C, the time is 15 min, the rotor speed is 60 rpm, and the mass of the Sb2MoO6 nanosheets is 1.0% of the total mass of the Sb2MoO6 nanosheets and the ABS resin matrix to obtain a modified ABS resin, which is recorded as ABS / AM1.
[0065] Application Examples 2 to 4
[0066] The preparation steps are the same as those in Application Example 1, with the only difference being that the mass of the Sb2MoO6 nanosheets is 3.0%, 5.0% and 10.0% of the total mass of the Sb2MoO6 nanosheets and the ABS resin matrix, respectively denoted as ABS / AM3, ABS / AM5 and ABS / AM10.
[0067] Structural characterization and performance testing
[0068] Fourier transform infrared spectrometer (FTIR, Nicolet-5700, USA) was used to analyze the chemical structure of nanomaterials and residual carbon; X-ray photoelectron spectrometer (XPS, KratosAXIS Ultra DLD, Japan) was used to analyze the chemical structure of nanomaterials; scanning electron microscope (SEM, Hitachi S-4800(II), Japan), transmission electron microscope (TEM, JEM-1230) and high-angle annular dark-field scanning transmission electron microscope (HAADF-STEM, Tecnai G2 F30 S-TWIN) equipped with energy dispersive X-ray (EDX) spectrometer were used to observe the sample morphology; X-ray diffractometer (XRD, Bruker AXSD8Advance, Germany) was used to study the chemical structure of nanoparticles and ABS nanocomposites.
[0069] The mechanical properties of the samples were tested using an AG-IS universal testing machine (ASTM D-638). The oxygen index (LOI) of the samples was measured using an oxygen index tester (PX-01-005, Phoenix, China) according to ASTM D2863. The combustion performance and smoke suppression performance of the samples were tested using a cone calorimeter (FTT, UK) according to ISO 5660-1. A Raman spectrometer (DXR2xi, ThermoScientific, USA) was used to study the graphitization degree of the carbon.
[0070] Structural characterization and performance testing of Sb2MoO6 nanosheets
[0071] Figure 1 The XRD pattern (a) and SEM image (b) of the Sb2MoO6 sample of Comparative Example 1. Figure 1 The product prepared by reacting for 12 h without adding CTAB is shown in a. Figure 3 Figure a shows the X-ray diffraction (XRD) patterns of the products prepared by adding CTAB for different reaction times, which all match well with the standard pattern of Sb2MoO6 (JCPDS 33-1491). No additional peaks were detected, indicating the high purity of the product. As the reaction time increases, the intensity of the diffraction peaks first becomes strong and then weak, among which the diffraction peak of AM-12h is the strongest.
[0072] Figure 2 SEM images of the Sb2MoO6 sample AM-6h (a) of Example 2, the Sb2MoO6 sample AM-9h (b) of Example 3, the Sb2MoO6 sample AM-12h (c) of Example 1, the Sb2MoO6 sample AM-15h (d) of Example 4, and the Sb2MoO6 sample AM-18h (e) of Example 5, Figure 2 Scale bars are all 1 μm. Figure 2 It can be clearly seen that the Sb2MoO6 prepared by adding CTAB at different times are all in the form of flakes of different sizes; Figure 1 In b, both flake and granular forms can be observed. Through XRD and SEM tests, combined with actual experimental conditions, the present invention determined that Sb2MoO6 nanomaterials were prepared by adding CTAB and reacting for 12 hours (the following test samples were all prepared under this condition).
[0073] Figure 3 The XRD spectra of the Sb2MoO6 samples synthesized at different reaction times in Examples 1 to 5 (a) are compared with the JCPDS database of Sb2MoO6, the full XPS spectrum of the Sb2MoO6 sample in Example 1 (b), the Sb3d of the Sb2MoO6 sample in Example 1 (c), the O1s of the Sb2MoO6 sample in Example 1 (d), and the Mo3d of the Sb2MoO6 sample in Example 1 (e). Among them, Figure 3 Figure b shows the X-ray photoelectron spectroscopy (XPS) spectrum of Sb2MoO6, all data have been calibrated by C1 s (284.6 eV). Containing C, O, Mo and Sb elements, the spectrum matches the spectrum previously reported in the literature. In the high-resolution spectrum of Sb ( Figure 3 In Figure c), the peak at 539.4 eV can be attributed to Sb 3d 3 / 2, and the broad peak centered at 530.1 eV can be divided into the Sb 3d 5 / 2 peak (from Sb metal and Sb oxide) and the O1s peak (from CO groups and carbonate-state SEI) due to the overlap between Sb 3d5 / 2 and O1s. Figure 3 As shown in (d), the peaks at 232.3 and 235.4 eV are attributed to Mo3d5 / 2 and Mo3d3 / 2.
[0074] Figure 4 TEM images (ac, h) of Sb2MoO6 of Example 1, STEM-HAADF image (d) of Sb2MoO6 of Example 1, and elemental images of Mo, Sb, and O in the corresponding regions (e-g), Figure 4 The scale bar of a is 1 μm, the scale bars of b~d are all 200 nm, and the scale bar of h is 5 nm. Figure 4 :From TEM images ( Figure 4 (a-c) further confirm the flake morphology of Sb2MoO6 particles. Figure 4 In (h), the lattice fringes of the (2-20) plane can be clearly observed with a spacing of 0.249 nm, further demonstrating the high crystallinity of the Sb2MoO6 sheet. Figure 4 Figure d shows the HAADF image of Sb2MoO6 nanosheets. Figure 4 Figures e to g show the distribution of Sb, Mo, and O elements.
[0075] Structural characterization and performance testing of ABS composite materials (i.e. modified ABS resin)
[0076] The ABS composite materials prepared in Application Examples 1 to 4 were placed in a mold, preheated at 205° C. for 6 min, and pressed at 12 MPa for 8 min to prepare thick sheets for subsequent testing.
[0077] Figure 5 TEM images of ABS / AM1 (a) of Application Example 1, ABS / AM5 (b) of Application Example 3, and ABS / AM10 (c) of Application Example 4; XRD patterns of pure ABS and ABS composites (d); stress-strain curves (e) and mechanical property parameter comparison diagrams of ABS / AM composites (f). Figure 5 The scale bars of a1~c1 are all 200nm, and the scale bars of a2~c2 are all 1μm. Figure 5 : The performance improvement of ABS composites depends on the dispersion of nano-additives. Figure 5 The dispersion of Sb2MoO6 in ABS matrix was studied in Figures a-c. At different addition amounts (1, 5 and 10 wt%), Sb2MoO6 nanosheets can be uniformly dispersed in ABS. At higher magnification ( Figure 5 In the XRD patterns (a2 to c2), the flake structure of Sb2MoO6 can be observed, and its size is about 0 to 500 nm. Figure 5 In (d), no characteristic peaks of Sb2MoO6 were observed. Based on the TEM and XRD results, it can be reasonably concluded that Sb2MoO6 can be well dispersed in the ABS matrix only by a simple melt mixing method.
[0078] Figure 5 Zhongehe Figure 5 Figure f shows the stress-strain curves and mechanical property parameter comparison diagrams of pure ABS and ABS composite materials, respectively. The specific data are statistically shown in Table 1.
[0079] Table 1 Comparison of stress-strain curves and mechanical properties of pure ABS and ABS composites
[0080] Sample name Tensile strength(MPa) Elongation at break (%) ABS 64.3±1.1 19.4±0.5 ABS / AM1 67.6±1.2 15.6±0.5 ABS / AM3 68.9±1.3 16.2±0.3 ABS / AM5 69.8±2.5 13.8±0.3 ABS / AM10 72.8±1.6 12.4±0.3
[0081] From Table 1 and Figure 5As shown in Figures e to f, the presence of Sb2MoO6 nanosheets increases the tensile strength of ABS, but slightly reduces the elongation at break. Compared with pure ABS resin, the ABS composite material blended with 10% Sb2MoO6 nanosheets shows an increase in tensile strength of about 13% and a decrease in elongation at break of about 34%. The significant enhancement in tensile strength is mainly due to the mechanical reinforcement effect of uniform Sb2MoO6 nanosheets in the polymer matrix.
[0082] Thermal Decomposition Behavior of ABS Composites
[0083] Pure ABS, pure Sb2MoO6 (ie Figure 6 The thermal decomposition behaviors of AM) and ABS composites in air are shown in Table 2. Figure 6 The relevant data are summarized in Table 2.
[0084] Table 2 Thermogravimetric data of ABS / AM composites
[0085] Sample name <![CDATA[T i a (℃)]]> <![CDATA[T max b (℃)]]> Residue at 600℃ (wt%) ABS 373 418 0.89 AM 358 - 94.19 ABS / AM1 370 419 1.95 ABS / AM3 371 425 4.18 ABS / AM5 372 423 6.85 ABS / AM10 372 416 10.02
[0086] a T i and b T max The temperatures are 5 wt% and the maximum thermal weight loss, respectively.
[0087] ABS is a copolymer composed of three components. It has two-stage decomposition when burning in air. The first stage is between 400 and 500°C. This stage can be considered as the disintegration of the double bond structure of ABS phase B and the oxidation of relatively unstable functional groups such as -CN bonds. The second stage is between 500 and 600°C. This stage is the decomposition of the remaining benzene rings and saturated hydrocarbon molecular chains in the previous stage. Figure 6 As shown in Table 2, pure ABS begins to degrade at 373°C and reaches the maximum degradation rate at 418°C. Pure Sb2MoO6 can be divided into three stages of combustion in air. The first stage is at 200-420°C, and oxidative decomposition is carried out on AM. In the second stage, at 420-680°C, the TG curve rebounds due to the oxides produced by combustion. In the third stage, at 680-800°C, oxidative decomposition occurs as the temperature increases, and the TG curve drops again. The addition of Sb2MoO6 has almost no effect on the initial decomposition temperature of the composite material. The addition of Sb2MoO6 promotes the carbonization of ABS composite materials, and the carbonization effect increases with the increase of the addition amount. For example, in an air environment at 600°C, the residual carbon rate of the ABS / AM10 sample reaches 10.02%. In addition, compared with other composites, the mass loss rate (MLRmax) of ABS / AM10 is at the lowest peak, which further confirms that Sb2MoO6 can improve the carbonization effect, thereby increasing the fire resistance of the underlying matrix.
[0088] Fire resistance of ABS composite materials
[0089] Cone calorimetry (CCT) testing is commonly used to evaluate the burning behavior of polymers when exposed to constant thermal radiation in realistic fire situations. Figure 7 (a) The heat release rate curves of ABS and ABS / AM samples of Application Examples 1 to 4, and (b) the smoke generation rate curves. Figure 7 Figures (a) and (b) show the heat release rate (HRR) and smoke release rate (SPR) curves, and the detailed data are summarized in Table 3. ABS shows 938kW / m 2 The peak heat release rate (PHRR) and 116MJ / m 2 The PHRR of ABS / AM1, ABS / AM5 and ABS / AM10 are reduced to 898kW / m 2 、753kW / m 2 and 629kW / m 2 , compared with pure ABS, they were reduced by 4.26%, 19.7% and 32.9% respectively. The THR of ABS / AM1, ABS / AM5 and ABS / AM / 10 were reduced to 115MJ / m 2 、111MJ / m 2 and 104MJ / m 2 , indicating that Sb2MoO6 has the effect of inhibiting combustion. In addition, the average mass loss rate (AMLR) decreases with the increase of Sb2MoO6 addition, indicating that the mass loss behavior of ABS / AM composites is inhibited to a certain extent, which can explain the significant increase in the residual carbon content of ABS / AM.
[0090] Smoke is one of the key factors leading to casualties in fires, so smoke generation data is crucial in evaluating the fire safety of materials. It can be seen that with the addition of 5wt% and 10wt% Sb2MoO6, the peak smoke release rate (PSPR) of ABS / AM5 and ABS / AM10 is significantly reduced. Compared with the PSPR of ABS, ABS / AM5 and ABS / AM10, the PSPR is reduced by 19.7% and 32.4%, respectively. The total smoke generation (TSP) of ABS, ABS / AM5 and ABS / AM10 is 16.96m 2 、16.52m 2 and 16.44m 2 Therefore, the addition of Sb2MoO6 can reduce the smoke hazard of ABS / AM.
[0091] Table 3 Cone calorimeter test data of ABS and ABS / AM samples
[0092]
[0093] TTI a : Ignition time, PHRR a : Peak heat release rate, THR a : Total heat release, AMLR a : Average mass loss rate, PSPR a : Peak smoke release rate, TSP a : Total smoke release.
[0094] Flame retardant mechanism
[0095] Table 4 EDX data of carbon residue of ABS composite materials
[0096]
[0097]
[0098] Figure 8 The SEM images of carbon residues of ABS / AM composite materials are shown in the following table: the upper and lower rows are ABS / AM1, ABS / AM5, and ABS / AM10. Figure 8 The scale bars in the upper row of graphs are 50.0 μm, and the scale bars in the lower row of graphs are all 5.0 μm. Fig. 9 The XPS full spectrum (b) and Sb3d (c), O1s (d) and Mo3d (e) spectra of the ABS / AM10 carbon residue of Application Example 4. Fig.10 FTIR spectra of carbon residues of ABS and ABS composite materials.
[0099] In order to analyze the condensed phase effect of Sb2MoO6, SEM-EDX ( Figure 8 , Table 4), FTIR( Fig.10 ) studied the cone calorimetry carbon residues of ABS and ABS / AM. ABS left only a very small amount of broken and brittle carbon after the test, further indicating its poor carbon-forming ability. With the addition of Sb2MoO6, the carbon structure became dense and continuous. The formation of this dense carbon helps to suppress the heat release and smoke generation during combustion. It is also worth noting that from the figure ( Figure 8 The flake structure material is well dispersed in the carbon layer. The XPS of ABS / AM10 carbon residue ( Fig. 9 ) The results confirmed that the flake material was Sb2MoO6 flake. In all FTIR spectra, the absorption peaks of OH and C=C bonds were located at 3440 cm -1 、1600cm -1 In addition to the above peaks, in the FTIR spectra of ABS / AM1, ABS / AM5, and ABS / AM10, there is a peak at about 760 cm -1The peak at can be attributed to the Mo-O absorption peak. These results further confirm that the Sb2MoO6 sheets act in the condensed phase during the combustion process, thereby improving the fire safety of ABS nanocomposites.
[0100] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing antimony molybdate nanosheets, characterized in that: The following steps are involved: The cationic surfactant, antimony salt, molybdate and water are mixed and subjected to a hydrothermal reaction to obtain the antimony molybdate nanosheets; the temperature of the hydrothermal reaction is 160-210°C.
2. The preparation method according to claim 1, characterized in that: The cationic surfactant includes one or more of cetyltrimethylammonium bromide, dodecyltrimethylammonium chloride and cetylpyridinium chloride; the molar ratio of the cationic surfactant to molybdenum in molybdate is (0.5-0.7):
1.
3. The preparation method according to claim 1, characterized in that: The antimony salt includes antimony trichloride and / or antimony nitrate; the molybdate includes one or more of sodium molybdate, ammonium molybdate and potassium molybdate; the molar ratio of antimony in the antimony salt to molybdenum in the molybdate is 2:(1-1.2).
4. The preparation method according to claim 1, characterized in that: The hydrothermal reaction time is 6 to 18 hours.
5. The antimony molybdate nanosheets prepared by the preparation method according to any one of claims 1 to 4, characterized in that: The diameter of the antimony molybdate nanosheet is ≤500nm.
6. A modified ABS resin, characterized in that: It comprises an ABS resin matrix and antimony molybdate nanosheets dispersed in the ABS resin matrix; the antimony molybdate nanosheets are the antimony molybdate nanosheets according to claim 5.
7. The modified ABS resin according to claim 6, characterized in that: The mass of the antimony molybdate nanosheets is 1-10% of the mass of the modified ABS resin.
8. The method for preparing the modified ABS resin according to claim 6 or 7, characterized in that: The following steps are involved: The antimony molybdate nanosheets and the ABS resin matrix are melt-blended to obtain the modified ABS resin.
9. The preparation method according to claim 8, characterized in that: The temperature of the melt blending is 180-210° C., and the time is 10-18 minutes.
10. Use of the modified ABS resin according to claim 6 or 7 or the modified ABS resin prepared by the preparation method according to claim 8 or 9 in flame retardancy and smoke suppression.